Flow karyotyping of wheat-Aegilops additions facilitate dissecting the genomes of Ae. biuncialis and Ae. geniculata into individual chromosomes - Said, Mahmoud; Cápal, Petr; Farkas, András; Gaál, Eszter; Ivanizs, László; Friebe, Bernd; Doležel, Jaroslav; Molnár, István (Frontiers in Plant Science, 2022)
Breeding of wheat adapted to new climatic conditions and resistant to diseases and pests is hindered by a limited gene pool due to domestication and thousands of years of human selection. Annual goatgrasses (Aegilops spp.) with M and U genomes are potential sources of the missing genes and alleles. Development of alien introgression lines of wheat may be facilitated by the knowledge of DNA sequences of Aegilops chromosomes. As the Aegilops genomes are complex, sequencing relevant Aegilops chromosomes purified by flow cytometric sorting offers an attractive route forward. The present study extends the potential of chromosome genomics to allotetraploid Ae. biuncialis and Ae. geniculata by dissecting their M and U genomes into individual chromosomes. Hybridization of FITC-conjugated GAA oligonucleotide probe to chromosomes suspensions of the two species allowed the application of bivariate flow karyotyping and sorting some individual chromosomes. Bivariate flow karyotype FITC vs. DAPI of Ae. biuncialis consisted of nine chromosome-populations, but their chromosome content determined by microscopic analysis of flow sorted chromosomes indicated that only 7Mb and 1Ub could be sorted at high purity. In the case of Ae. geniculata, fourteen chromosome-populations were discriminated, allowing the separation of nine individual chromosomes (1Mg, 3Mg, 5Mg, 6Mg, 7Mg, 1Ug, 3Ug, 6Ug, and 7Ug) out of the 14. To sort the remaining chromosomes, a partial set of wheat-Ae. biuncialis and a whole set of wheat-Ae. geniculata chromosome addition lines were also flow karyotyped, revealing clear separation of the GAA-rich Aegilops chromosomes from the GAA-poor A- and D-genome chromosomes of wheat. All of the alien chromosomes represented by individual addition lines could be isolated at purities ranging from 74.5% to 96.6% and from 87.8% to 97.7%, respectively. Differences in flow karyotypes between Ae. biuncialis and Ae. geniculata were analyzed and discussed. Chromosome-specific genomic resources will facilitate gene cloning and the development of molecular tools to support alien introgression breeding of wheat.